Dragonflies on the Islands in the Straits of Malacca - Norma-Rashid, Yusoff; Sofian-Azirun, Mohd; Ramli, R.; Hashim, R. (Faculty of Science, University of Malaya, 2008)
The odonate fauna of Pulau Perak, Pulau Jarak and some islands of the Sembilan group of islands were surveyed. Although no endemics were found, fifteen species, all first records for the islands were documented. Various biological aspects of the dragonfly such as population, distribution and relative abundance were discussed. Morphometric aspects were also studied and possible explanations for the attributed differences between the island populations of Pulau Perak and Pulau Lalang are proposed.